2008
DOI: 10.1093/ndt/gfm917
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of MK2 signalling in vivo inhibits small Hsp phosphorylation but not diabetic nephropathy

Abstract: It is supposed that some stress-induced heat shock proteins (Hsps) are regulated through e.g. stimulation of the p38MAPK/MK(MAPKAP)-2 signalling pathway. It has been postulated from in vitro experiments that phosphorylation of Hsp25(rodents)/Hsp27(human), the major phosphorylation substrate of MK2, is responsible for mesangial contractility and glomerular hyperfiltration in the diabetic kidney. To verify this hypothesis in vivo we studied the renal function of nondiabetic and streptozotocin (STZ)-induced, diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Both the pattern of staining and costaining with the podocyte marker synaptopodin suggest a localization to the glomerular podocytes. Previous studies have reported an increase in the phosphorylated form of HSP25 in the diabetic glomeruli (6,21,23), but this is the first study that identifies the specific glomerular cell type involved. Furthermore, our in vitro data show that podocyte exposure to stretch, mimicking glomerular capillary hypertension, induces a rapid and significant 4.4-fold increase in the levels of phosphorylated HSP27.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Both the pattern of staining and costaining with the podocyte marker synaptopodin suggest a localization to the glomerular podocytes. Previous studies have reported an increase in the phosphorylated form of HSP25 in the diabetic glomeruli (6,21,23), but this is the first study that identifies the specific glomerular cell type involved. Furthermore, our in vitro data show that podocyte exposure to stretch, mimicking glomerular capillary hypertension, induces a rapid and significant 4.4-fold increase in the levels of phosphorylated HSP27.…”
Section: Discussionmentioning
confidence: 77%
“…In contrast, Park et al (23) have recently reported that albuminuria is not ameliorated in diabetic mice knockout for MK2. However, in this study HSP27 phosphorylation was only partially prevented, and it is known that not only MK2, but also MK3 can phosphorylate HSP27 on the same serine residues (4).…”
Section: Discussionmentioning
confidence: 84%
“…57 Indeed, high glucose promotes HSPB1 phosphorylation in renal cells in an MK(MAPKAP)-2-dependent manner. 58 The phosphorylation state of HSPB1 can influence its function. Thus, it modulates the size of HSPB1 oligomers and facilitates the nuclear migration of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46] 44 HSP25 is phosphorylated by upstream p38 mitogenactivated protein kinase (p38MAPK). [47][48][49] A study showed synchronized activation of the glomerular p38MAPK-HSP25 pathway, acutely after the induction of diabetes with streptozotocin (Stz-DM) in rats, together with conservation of the podocyte actin cytoskeleton and normo-albuminuria.…”
Section: Hsp27 In Diabetic Nephropathymentioning
confidence: 99%
“…54 Animal models of nephrotic syndrome and DN showed enhanced HSP27 phosphorylation compared to control animals. 44,46,55 Abnormal HSP27 phosphorylation is also observed in renal cancers, as well as in other kidney diseases. 56 Furthermore, over-expression of HSP27 has been contributed to tumor progression in a variety of cancers including Renal Cell Carcinoma (RCC).…”
Section: Abnormal Hsp27 Phosphorylation In Kidney Diseasementioning
confidence: 99%